2019
DOI: 10.14202/vetworld.2019.584-592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonality on the population density of wetland aquatic insects: A case study of the Hawr Al Azim and Shadegan wetlands, Iran

Abstract: Aim: Wetlands are extremely suitable ecosystems to assess the effect of climate change on the density of aquatic insects. This study aimed to assess the effect of seasonality on populations of aquatic insects in the Hawr Al Azim and Shadegan wetlands. Materials and Methods: The insect samplings were conducted at a large area of the Hawr Al Azim and five different sites of the Shadegan wetlands. In total, 18,534 arthropods of different life stages, including 12 orders containing 51 families, were collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In Turkey, which has a common border with western Iran, the peak of CCHF cases was seen around June and July and the number of patients was related to the previous year's meteorological conditions which affected the vectors [12]. Studies have shown increasing populations of ticks and their related diseases in relation to climate change [31,32] . Ticks usually live in warm temperatures [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, which has a common border with western Iran, the peak of CCHF cases was seen around June and July and the number of patients was related to the previous year's meteorological conditions which affected the vectors [12]. Studies have shown increasing populations of ticks and their related diseases in relation to climate change [31,32] . Ticks usually live in warm temperatures [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown increasing populations of ticks and their related diseases in relation to climate change [ 31 , 32 ] . Ticks usually live in warm temperatures [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity trend lines of N. crispa essential oil and propoxur against invertebrate (Sf9) and vertebrate (L929) cell lines were estimated by Microsoft Excel version 2013. The trend lines were drawn by clicking on graph line distribution and selecting "add trendline" option using procedure described in previous studies [17][18][19][20][21][22][23][24][25][26][27][28].The equations and R-squared values of the cytotoxicity trend lines were also calculated by Microsoft Excel. IBM SPSS statistics data editor version 24 was used for any statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The trends of malathion and N. crispa essential oil cytotoxicity against L929 and Sf9 cell lines was estimated by Microsoft Office Excel 2013. The trends were drawn by clicking on graph line distribution and selecting “add trendline” option using Nasirian and Salehzadeh (2017a, b; 2019a, b) style [11, 37-40].…”
Section: Methodsmentioning
confidence: 99%